High Frequency Model of the COVID-19 Pandemic in Ireland and its Trading Partners During 2020 - Smith, Donal; Rehill, Luke; Shu, Haicheng (Statistical and Social Inquiry Society of Ireland, 2021)
The COVID-19 pandemic represents a complex challenge to policymakers from both a public health and economic perspective. It has caused a severe economic shock to both the Irish and global economy with shutdown measures implemented in most economies. This paper describes a high frequency database and model developed from both the econometric and medical literature to provide a relative measure of the path of the pandemic in Ireland and across the globe with the aim of adding to the real time evidence for policy makers. Model estimates are reported for the critical early and peak stages of the pandemic. The pandemic is modelled as a stochastic difference equation. The logistic form is chosen as it is found to be the most practical model with the flexibility to provide daily estimates for a large set of countries on a key aspect of the pandemic, the steepness of the curve. This characteristic of the pandemic, whereby a steep rise in cases results in “flatten the curve” policy responses, is most closely associated with a suppression of economic activity. As a small open economy, it is critical for policy makers in Ireland to track developments in external demand. It is a key variable that frames scenario analysis and forecasting for government budgeting. The high-frequency database and time series model developed in this paper provides a real time relative indicator of potential economic impacts from the global spread of COVID-19 by estimating well known properties of functions. In the early stages of the pandemic the model estimated a high value of steepness of the curve for Spain and Italy and a low level for Korea. Ireland’s measure showed a trend decline, in line with countries such as Denmark and Austria. As the situation improved in Ireland model estimates provided an early indication of a deteriorating situation in some of Irelands main trading partners indicating a more prolonged economic impact. Second wave estimates indicated lockdown measure would persist throughout 2020 in large European trading partners.
read before the Society, 27th May 2021
Keywords: COVID-19; economic impact; small open economy; trading partners; 314.15